Venetoclax and Decitabine in Pediatric Refractory T-cell Lymphoblastic Lymphoma. Issue 7 (October 2021) - Baig, Muhammad U.; Rytting, Michael; Roth, Michael; Morani, Ajaykumar C.; Nunez, Cesar; Lin, Pei; Cuglievan, Branko
Abstract : Background: Overall survival of adolescents with relapsed T-cell lymphoblastic lymphoma (T-LL) remains poor with limited options for salvage therapy. The BCL-2 inhibitor venetoclax combined with hypomethylating agents like decitabine, has shown favorable responses in elderly patients with acute myeloid leukemia. Observation: We present the case of a 19-year-old adolescent with stage III relapsed and refractory T-LL who did not respond to 3 lines of salvage therapy. The patient was treated with venetoclax and decitabine and achieved a dramatic response. Conclusion: This case highlights the potential clinical activity of venetoclax and decitabine in relapsed T-LL.